Morphological and Pathogenic Variability among Macrophomina phaseolina Isolates Associated with Mungbean (Vigna radiata L.) Wilczek from Pakistan. (15th January 2014) - Iqbal, Umer; Mukhtar, Tariq
Abstract : Macrophomina phaseolina is a serious pathogen of many crops. In the present studies, 65 isolates of Macrophomina phaseolina from different agroecological regions of Punjab and Khyber Pakhtunkhwa provinces of Pakistan were analyzed for morphological and pathogenic variability. Regardless of their geographic origins, significant differences were detected among 65 isolates in their radial growth, sclerotial size, and weight as well as in pathogenicity. Sixteen isolates were rated as fast growing, 11 as slow growing, and the rest of the isolates as medium growing. Nine isolates were classified as large sized, 26 as small sized, and the remaining 30 isolates as medium sized. Thirty five isolates were ranked as heavy weight, 12 as low weight, and the rest of isolates were grouped as medium weight. Ten fungal isolates appeared to be least virulent, whereas eight isolates of diverse origin proved to be highly virulent against mungbean cultivars. The remaining isolates were regarded as moderately virulent. No relationship was found among the morphological characters and pathogenicity of the isolates. These morphological and pathogenic variations in various isolates of M. phaseolina may be considered important in disease management systems and will be useful in breeding programmes of mungbean cultivars resistant to charcoal rot.